A tributação da parcela do ajuste do investimento em controlada situada em país com o qual o Brasil possui acordo de bitributação: uma análise constructivista lógico-semântica - Martins, Bruce Bastos (2019)
The economically globalized world is, above all, an environment characterized by trade relations, in which countries seek to assert their sovereignties within a dynamic context of transnational circulation of the incomes produced. As an integral part of this scenario, the economically involved countries end up causing double taxation of the circulated wealth: once in the country of the source of their production and another in the country of residence of the taxpayer. Because of this, international agreements are established to prevent two countries from taxing the same presumptive sign of wealth, based on rules aimed at regulating tax competent jurisdiction. Therefore, the objective of this work is to identify, through the method of logical-semantic constructivism, the difference between the profit earned by a controlled company abroad and its reflection in the equity of the brazilian controlling company, and to point out that this is a legal fact that does not subsume to the tax hypotheses established in Articles 7 and 10 of the OECD MT. As a side effect, the concepts of company profits and dividends established in the double taxation agreement, as well as the definition of taxable profit in Brazilian legislation will be delineated analytically, in the construction of the tax norm, in order to discern the distinction between the controlled company's profit abroad and the profits of the the controlling company in Brazil, and conclude that taxable profit is not an economic phenomenon, but a legal reality constituted by the fictional language of law